TENSILE BEHAVIOR OF SINGLE ELBOW ASSEMBLY WITH RIVETS ORIENTATION ON JUTE/EPOXY COMPOSITE - I.G.L, Aditya Pradnyana; I.G.K, Dwijana; I.D.G, Ary Subagia (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
This experiment's purpose is to investigate the tension strength of the elbow joint with the variation of rivets position. The Joining was made based on jute woven fabric reinforced composite epoxy. The vacuum-assisted resin transfer molding process was employed to manufacture composites. In this joint two rivets were used in three orientations of positions such as diagonal (D), Vertical (V), and horizontal (H). In order to investigate the properties of a sample, the tensile loading was carried out. Then, the failure of samples based on the photographic method has analyzed. The test result shows that the tensile strength of joints with D orientation has the highest value compared with rivets on orientation V and H are 3.329 MPa, 2.946 MPa, dan 2.737 MPa, respectively. Additionally, the shear stress value of each rivets orientation on tangential states have D = 59.49 N/mm2, V = 47.46 N/mm2, and H = 45.35 N/mm2, respectively. It can be concluded that the rivet state orientation becomes an important factor for the tension strength of the tangential joint of the composites.